2010
DOI: 10.1111/j.1474-9726.2009.00544.x
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 protects against pathological damage caused by diet‐induced obesity

Abstract: SummaryThe NAD+-dependent SIRT6 deacetylase is a therapeutic candidate against the emerging metabolic syndrome epidemic. SIRT6, whose deficiency in mice results in premature aging phenotypes and metabolic defects, was implicated in a calorie restriction response that showed an opposite set of phenotypes from the metabolic syndrome. To explore the role of SIRT6 in metabolic stress, wild type and transgenic (TG) mice overexpressing SIRT6 were fed a high fat diet. In comparison to their wild-type littermates, SIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
224
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(238 citation statements)
references
References 45 publications
13
224
1
Order By: Relevance
“…Other members of the sirtuin gene family have been shown to be amenable to pharmacological stimulation (34,35), and recent reports have suggested that SIRT6 may be an intriguing candidate for activation to ameliorate the effect of multiple age-related pathologies. In addition to lifespan extension, a separate study indicated that SIRT6 overexpression protects against diet-induced obesity (36). Additionally, we have observed that SIRT6 overexpression is selectively cytotoxic to multiple cancer cell lines (37), and several studies have suggested that SIRT6 may function as an agonist of NF-κB-induced inflammation (38,39).…”
Section: Discussionmentioning
confidence: 88%
“…Other members of the sirtuin gene family have been shown to be amenable to pharmacological stimulation (34,35), and recent reports have suggested that SIRT6 may be an intriguing candidate for activation to ameliorate the effect of multiple age-related pathologies. In addition to lifespan extension, a separate study indicated that SIRT6 overexpression protects against diet-induced obesity (36). Additionally, we have observed that SIRT6 overexpression is selectively cytotoxic to multiple cancer cell lines (37), and several studies have suggested that SIRT6 may function as an agonist of NF-κB-induced inflammation (38,39).…”
Section: Discussionmentioning
confidence: 88%
“…Mice with a liver-specific deletion of Sirt6 develop a fatty liver, and primary hepatocytes from these mice show relatively low levels of fatty acid oxidation. By contrast, mice with transgenic overexpression of SIRT6 show down-regulation of genes associated with lipid storage and are somewhat protected against the accumulation of visceral fat when placed on a high-fat diet (32). These studies cast Sirt6 as an important promoter of fat utilization.…”
Section: Metabolismmentioning
confidence: 86%
“…Similarly, Sirt2 does inhibit adipogenesis and accumulation of lipids in 3T3-L1 adipocytes by deacetylation of FOXO1, which represses PPARγ (10). The role of Sirt6 in the regulation of adipogenic differentiation is less clear although it is known that Sirt6 knockout (KO) mice suffer from reduced adipose tissue stores, while Sirt6 overexpressing mice are protected against high-fat diet-induced obesity (11,12). Interestingly, Sirt1 and Sirt6 both mediate effects of rosiglitazone on hepatic lipid accumulation (13).…”
mentioning
confidence: 99%